Motif Komunikasi Mahasiswa UIN Ar-Raniry dalam Menulis Artikel di Media Massa - Balqis Saldevi, Putri; Furqany, Syahril; Ramdan Sulaeman, Arif (Da’watuna: Journal of Communication and Islamic Broadcasting, 2026)
The practice of writing articles in mass media among students has not been fully understood in terms of communication motives and subjective meanings that underlie the act of writing, even though writing ability is an important communication skill. Writing is one of the things that is inherent in students because in academic activities writing is a skill that is almost always needed. Such as making papers, reports, research results and many other student activities that require writing skills. This study aims to understand the communication motives of UIN Ar-Raniry students in writing articles in mass media using the perspective of Alfred Schutz’s motive theory. The study used a descriptive qualitative approach with a phenomenological method. Data were collected through semi-structured interviews with nine students from nine faculties who had published articles in mass media and were analyzed using the Miles and Huberman model (the sample was written in what way). The results showed that student communication motives were divided into two categories: because motive (motive cause) which includes the academic environment, the role of lecturers, organizational involvement, and family influence; and in-order-to motive (motive goal) which is to disseminate information and provide understanding to readers to form social awareness. These two motives are interrelated and form the wholeness of student communication actions. The study concluded that the activity of writing articles in the mass media is a meaningful social action that is carried out consciously, formed through past experiences and directed at certain communicative goals, and is a form of active participation of students in social discourse and public discourse.